Peningkatan Pengetahuan Masyarakat tentang Penggunaan Obat yang Rasional melalui Edukasi Pengenalan Obat - Dian Ayu Juwita; Elsa Badriyya; Lailaturrahmi Lailaturrahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
One of the factors influencing the level of drug usage is the level of knowledge. Knowledge is an essential aspect in shaping concrete actions. In society, various issues related to drug usage often arise due to a lack of understanding and incorrect behaviours regarding drug usage. Educating the public about the selection and rational use of drugs is compulsary cause of that. This activity was carried out on May 7, 2023, at Jondul Housing, Padang City. The education method employed was a lecture delivered to 35 participating mothers. This method has proven effective for all segments of society, regardless of their educational background. The general public showed high enthusiasm in participating and actively engaged in interactions, asking questions, and discussing with the speaker. The conclusion drawn from this activity is that education and outreach enhanced the public knowledge about the rational use of drugs.